STRATEGIC GOALS OF THE SYRDARYA REGION OF THE RUSSIAN EMPIRE (EARLY 20TH CENTURY) (Archive of Conferences, 2021)
The period of political and economic decline began when the country, which became famous during the reign of Timurids, was divided into three parts. In European countries, the way of governing the state has been modernized; the growth of science and technology, the production of weapons, and the capacity of self-defense have risen to a higher level than in the East. The Uzbek khanates continued to weaken. Moreover, diplomatic relations between them have significantly weakened. The struggle for power and popular discontent has further weakened the position of these states. In the context of these reforms, the old production relations were preserved.